The genomes of three Bradyrhizobium sp. isolated from root nodules of Lupinus albescens grown in extremely poor soils display important genes for resistance to environmental stress - Camille E. Granada (Genetics and Molecular Biology, 2018)
Abstract Lupinus albescens is a resistant cover plant that establishes symbiotic relationships with bacteria belonging to the Bradyrhizobium genus. This symbiosis helps the development of these plants in adverse environmental conditions, such as the ones found in arenized areas of Southern Brazil. This work studied three Bradyrhizobium sp. (AS23, NAS80 and NAS96) isolated from L. albescens plants that grow in extremely poor soils (arenized areas and adjacent grasslands). The genomes of these three strains were sequenced in the Ion Torrent platform using the IonXpress library preparation kit, and presented a total number of bases of 1,230,460,823 for AS23, 1,320,104,022 for NAS80, and 1,236,105,093 for NAS96. The genome comparison with closest strains Bradyrhizobium japonicum USDA6 and Bradyrhizobium diazoefficiens USDA110 showed important variable regions (with less than 80% of similarity). Genes encoding for factors for resistance/tolerance to heavy metal, flagellar motility, response to osmotic and oxidative stresses, heat shock proteins (present only in the three sequenced genomes) could be responsible for the ability of these microorganisms to survive in inhospitable environments. Knowledge about these genomes will provide a foundation for future development of an inoculant bioproduct that should optimize the recovery of degraded soils using cover crops.